2016
DOI: 10.1177/0145721716628649
|View full text |Cite
|
Sign up to set email alerts
|

Educational Needs and Technological Preferences of Fathers of Youth With Type 1 Diabetes

Abstract: The findings contribute to our understanding of the educational needs of fathers of children with T1DM and provide preliminary support for the acceptability of delivering diabetes education via mobile technology. The incorporation of patient and caregiver perspectives into the development of mHealth diabetes education applications may increase engagement and improve health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The quantitative survey results, published elsewhere [7], revealed that fathers of children with T1D had unmet diabetes education needs, including on topics in basic management such as managing hyperglycemia and hypoglycemia and calculating insulin doses, and more nuanced knowledge requirements, including managing diabetes at school, information on emerging diabetes technologies, and finding help for diabetes challenges. There was a high level of interest in online and mobile access to diabetes education resources [7]. The semistructured interview guide (Multimedia Appendix 1) was designed to elicit detailed information on the educational needs and design preferences of participants.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The quantitative survey results, published elsewhere [7], revealed that fathers of children with T1D had unmet diabetes education needs, including on topics in basic management such as managing hyperglycemia and hypoglycemia and calculating insulin doses, and more nuanced knowledge requirements, including managing diabetes at school, information on emerging diabetes technologies, and finding help for diabetes challenges. There was a high level of interest in online and mobile access to diabetes education resources [7]. The semistructured interview guide (Multimedia Appendix 1) was designed to elicit detailed information on the educational needs and design preferences of participants.…”
Section: Methodsmentioning
confidence: 99%
“…Push technology capability (the ability to push links to educational material to the end user via text or email) was facilitated via inclusion of a plug-in to automate this process. Content was informed by the phase 1 qualitative analysis and quantitative data on fathers’ educational needs and technological preferences reported elsewhere [7].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations